Design and Kinematics Analysis of a 3-DOF Translational Parallel Mechanism - Yu Liang; Zhang Long; Wang Peng; Wan Jun (Jixie chuandong)
A systemic research on configuration design and kinematics analysis of a new 3-DOF translational parallel robot， Delta， which involved T-type hinges， is carried out based on Delta widely used in food fields， pharmaceutical fields， electronic fields and other light industry. The displacements characteristics of minimal branch are obtained based on analysis of the freedom constraints relationship. And some branch types 3T0R parallel mechanism may contain are selected prudently. And some 3-DOF translational parallel robot mechanisms are synthesized. New Delta parallel robot mechanism that contains T-type hinges is synthesized by mechanism evolution method， whose branch type is <alternatives>HSOC<mtext>{</mtext><mtext>-</mtext>P<mtext>(</mtext>4R<mtext>)</mtext><mtext>-</mtext><mover accent="true">R<mtext>⊥</mtext>R<mtext>̑</mtext></mover><mtext>/</mtext><mtext>/</mtext><mover accent="true">R<mtext>⊥</mtext>R<mtext>̑</mtext></mover><mtext>-</mtext><mtext>}</mtext> <?fx-imagestate width="54.94866943" height="4.14866638"?> <?fx-imagestate width="54.94866943" height="4.14866638"?> </alternatives>. And based on the displacement parameter characteristics， the spatial degree of freedom is checked. Finally， the kinematics analysis of Delta parallel robot mechanism is carried out. And the inverse position model， forward position model and velocity model are built.